Efficient Broadcast Time-Stamping - Benaloh, Josh; Mare, Michael de (Microsoft, 1991)
Even using an authenticated synchronous broadcast model, the task of unforgeably time-stamping digital documents still presents some problems. It is simply not practical to assume that all participants will record and store everyone else's documents so that creation times can be verified. This paper presents a time and space effecient method for accumulation of time-stamped documents. Whenever a question arises, a claimant can convince any "honest" participant of the time that its document was posted.